Bez retushi . Bez retushi . Without Retouching . Без ретуши - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the politician Aleksandr Pochinok about budget policy in Russia. Featured in the program: Pochinok, Aleksandr Petrovich (Committee Chairman for Budget, Planning, Taxes and Prices of the Soviet of the Republic of the Supreme Soviet of the Russian Supreme Soviet) Contributors: Torchinskii, Sergei (Anchor); Krasnova, Tat'iana (Anchor) Интервью с политиком Александром Починком о бюджетной политике в России. В программе участвуют: Починок, Александр Петрович (Председатель Комиссии по бюджету, планам, налогам и ценам Совета Республики Верховного Совета России) Создатели: Торчинский, Сергей (Ведущий/Ведущая); Краснова, Татьяна (Ведущий/Ведущая)